Tati, PERENCANAAN MANAJEMEN PROYEK SISTEM INFORMASI AKUNTANSI KEUANGAN DAERAH MENGGUNAKAN FRAMEWORK ITPOSMO - Humdiana Roelly S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2012)
This study aims to present a project management planning of the of the local financial accounting information system (SIMAKDA) overall by using the framework ITPOSMO. The methodology used in this study based on the PMI process group. For data analysis used framework ITPOSMO, Work Breakdown Structure (WBS) and Microsoft Project software to design the project scheduling and cost estimates. First step in research is collect the data, primary and secondary data. This is done by using the method of field studies and literature study. Literature study carried out by studying books and liteatur related to research themes, whereas the field study conducted by the study of documents and interviews of the parties associated with the project SIMAKDA. The results of the study was a project can be run in accordance with the schedule and budget that has been determined and the Regional Financial Information System can be implemented properly. SIMAKDA Implementation is expected to increase the area of financial management so that the regional development goes well in order to improve public welfare Banjar area, East Kalimantan.